'Birds without legs': legal integration as potentiality for women of an Afghan-Turkmen family in Istanbul. Issue 1 (2nd January 2023) - Ibañez-Tirado, Diana; Latif Khan, Rabia
ABSTRACT: This article examines how three generations of women in an Afghan–Turkmen family residing in Istanbul, Turkey, have experienced historical migration and legal integration. We deploy the concept of potentiality to convey these women's experiences of legal integration as a particular form of existence that is, at times, expressed by them and other families of Afghan background with the Dari metaphor of being 'birds without legs'. The metaphor conveys their constant mobility. Combining original ethnographic data with the analysis of historical works, we argue that families of Turkic ethnolinguistic backgrounds from Afghanistan residing in Turkey have been unable, and at times unwilling, to realize refuge, citizenship and settlement as the endpoint of their mobile trajectories.